Recent Publications (Quarterly Journal of Economics, 1961)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 75, Issue 1, February 1961, Pages 167–172, https://doi.org/10.1093/qje/75.1.167 Published: 01 February 1961